Effect of the postharvest storage period on the dry matter content and chemical composition of the cactaceae forages - dos Santos, Mércia Virgínia F.; Lira, Mário de A.; Farias, Iderval; Burity, Hélio A.; Filho, José J. Tavares (Pesquisa Agropecuaria Brasileira, 1992)
The experiment was conducted with the objective of evaluating different periods of post-harvest storage of the cladodes (zero, four, eight, twelve and sixteen days) stored after cut under lateral side open warehouse. The cladodes of three cultivars Opuntia ficus indica cvs. «Redonda» and «Gigante» and one of Nopalea cochenillifera cv. «Miúda» were tested in five postharvest storage times in a complete block design. The results demonstrated that the cladodes in all the postharvest storage periods were fairly similar in respect to: percentage of dry matter, crude protein, crude fiber and soluble carbohydrates. The data suggest that the cladodes may be stored for periods of up to 16 days for consumption without considerable losses of their nutritive characteristics. This will result in decreasing cutting and storing costs.